Improvement medicine adherence on quality of life in hypertension patients - Sriyati Sriyati; Abdul Latif (Universitas Muhammadiyah Semarang, 2023)
Hypertensive patients who do not take medication therapy for a long time will cause complications that will cause discomfort and affect their quality of life. This condition can be prevented and treated by having routine drug therapy. This study aims to determine the relationship between medication adherence and quality of life in hypertensive patients at the Mantrijeron Health Center, Yogyakarta. This research was a quantitative study using a cross-sectional design. The sample was taken using a purposive sampling technique with 74 respondents being hypertensive patients. The data collection instruments were the medication adherence report scale and the World Health Organization Quality of Life questionnaire. Bivariate analysis used the Pearson's correlation test which showed p = 0.027 (<0.05). These results indicate a significant relationship between medication adherence and the quality of life of hypertensive patients. The conclusion of this study is that there is a relationship between medication adherence and the quality of life of hypertensive patients. it is suggested that increasing medication adherence among hypertension patients can improve their quality of life.